Novel key management and authentication scheme for ad hoc space networks - YANG De-ming; MU De-jun; XU Zhong (Tongxin xuebao)
To be implemented using a flexible distributed architecture consisting of a constellation of dynamically de-ployed or configured satellites that were networked together into an integrated information system,the satellites could form an ad hoc self-organizational network,which posed unique challenges to security for the network.A novel and flexible security architecture was proposed,which aimed to provide public key infrastructure and authentication scheme.Based on the absolute distributed certificate authority almost any standard public-key-based authentication protocol could be adopted directly.In cases where the space nodes involved were extremely limited in computational resources,a light-weight authentication scheme that provided integrity and confidentiality based on cryptographic hash functions and symmetric key cryptography was proposed.